2004
DOI: 10.1111/j.1461-0248.2004.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Species–energy relationships and habitat complexity in bird communities

Abstract: Species-energy theory is a commonly invoked theory predicting a positive relationship between species richness and available energy. The More Individuals Hypothesis (MIH) attempts to explain this pattern, and assumes that areas with greater food resources support more individuals, and that communities with more individuals include more species. Using a large dataset for North American birds, I tested these predictions of the MIH, and also examined the effect of habitat complexity on community structure. I foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
341
5
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(383 citation statements)
references
References 34 publications
27
341
5
10
Order By: Relevance
“…Not surprisingly, avian diversity along the Panama Canal showed a response to plant species richness, probably because of associated higher vegetation complexity, higher arthropod diversity and diversity of ecological niches (MacArthur et al, 1962;MacArthur, 1964;Terborgh & Weske, 1969;Ricklefs & Schluter, 1993;Siemann et al, 1998;Gillespie & Walter, 2001;Waltert et al, 2003Waltert et al, , 2005Hurlbert, 2004;Tews et al, 2004). Higher rainfall, relating to higher plant diversity in the Panama Canal region, can be a good indicator of ecosystems with a higher productivity (Kaspari et al, 2000;Clark et al, 2001;Hawkins et al, 2003Hawkins et al, , 2005Santiago & Mulkey, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, avian diversity along the Panama Canal showed a response to plant species richness, probably because of associated higher vegetation complexity, higher arthropod diversity and diversity of ecological niches (MacArthur et al, 1962;MacArthur, 1964;Terborgh & Weske, 1969;Ricklefs & Schluter, 1993;Siemann et al, 1998;Gillespie & Walter, 2001;Waltert et al, 2003Waltert et al, , 2005Hurlbert, 2004;Tews et al, 2004). Higher rainfall, relating to higher plant diversity in the Panama Canal region, can be a good indicator of ecosystems with a higher productivity (Kaspari et al, 2000;Clark et al, 2001;Hawkins et al, 2003Hawkins et al, , 2005Santiago & Mulkey, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Specific examples include the increase in plant and bird diversity with variation in mean annual rainfall (Gentry, 1982;Cueto & Lopez de Casenave, 1999;Gillespie & Walter, 2001;Hawkins et al, 2005;Schnitzer, 2005), topographic complexity and variability of elevation (Kerr & Packer, 1997;Kerr et al, 2001;Rahbek & Graves, 2001). Many potential explanations for diversity gradients have been proposed, including speciesenergy relationships (Hurlbert & Haskell, 2003;Hurlbert, 2004), habitat heterogeneity-animal species diversity relationships (Kerr & Packer, 1997;Tews et al, 2004) and historical factors (Ricklefs & Schluter, 1993;Ricklefs, 2004;Hawkins et al, 2006). Few studies have examined relationships across small geographical areas in the species-rich tropics.…”
Section: Introductionmentioning
confidence: 99%
“…'Resource Specialization Hypothesis' argues that increased plant diversity provides a greater diversity of resources which favours an increase in consumer species richness due to an accumulation of consumers specializing on different resources [16,17].…”
Section: The Predictive Role Of Producer and Consumer Traits Plant Trmentioning
confidence: 99%
“…A rich body of theory has been developed to predict the effects of plant diversity on communities at higher trophic levels ( [16][17][18][19][20][21][22], see Box 1). Despite this vast collection of theory behind plant diversity effects on associated faunas and the large number of empirical studies conducted thus far, formal evaluations of the mechanisms behind the observed patterns have been developed in natural communities (but see [20] for e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation